2021
DOI: 10.20517/2347-9264.2020.176
|View full text |Cite
|
Sign up to set email alerts
|

Current and future trends in periodontal tissue engineering and bone regeneration

Abstract: Periodontal tissue engineering involves a multi-disciplinary approach towards the regeneration of periodontal ligament, cementum and alveolar bone surrounding teeth, whereas bone regeneration specifically applies to ridge reconstruction in preparation for future implant placement, sinus floor augmentation and regeneration of peri-implant osseous defects. Successful periodontal regeneration is based on verifiable cementogenesis on the root surface, oblique insertion of periodontal ligament fibers and formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 155 publications
0
38
0
1
Order By: Relevance
“…As an aid for alveolar ridge preservation, the use of barrier membranes in combination with bone grafts during ARP procedures was demonstrated to prevent epithelial downgrowth into the alveolar socket, whereas the graft material avoids membrane collapse and promotes bone formation through osteoconduction and/or osteoinduction processes [ 87 ]. Resorbable collagen matrices are the membranes of choice to cover ABXs-grafted sockets, with conflicting outcomes reported by clinical trials which demonstrated both (a) the effective reduction of horizontal ridge changes, with significant preservation of vertical height at mid crest [ 73 ] and (b) failure to limit the loss of horizontal/vertical ridge dimensions in comparison with the application of collagen membrane without ABXs [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…As an aid for alveolar ridge preservation, the use of barrier membranes in combination with bone grafts during ARP procedures was demonstrated to prevent epithelial downgrowth into the alveolar socket, whereas the graft material avoids membrane collapse and promotes bone formation through osteoconduction and/or osteoinduction processes [ 87 ]. Resorbable collagen matrices are the membranes of choice to cover ABXs-grafted sockets, with conflicting outcomes reported by clinical trials which demonstrated both (a) the effective reduction of horizontal ridge changes, with significant preservation of vertical height at mid crest [ 73 ] and (b) failure to limit the loss of horizontal/vertical ridge dimensions in comparison with the application of collagen membrane without ABXs [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…In other studies using spray-dried mesoporous bioactive glass microspheres [ 41 ] or pure mesoporous silicate nanoparticles [ 42 ], the protein amount was significantly higher in relation to MSN mass, thus yielding higher loading capacity. However, the exact dose of rhBMP-2 that can promote bone regeneration in different clinical applications without adverse effects has yet to be discovered, as different studies have reported controversial findings [ 43 , 44 , 45 ], increasing the reluctance and insecurity of clinicians to apply it [ 46 , 47 ]. It has not been proven that a high dose of rhBMP-2 can increase its efficacy [ 48 ], instead it can lead to increased inflammation [ 49 , 50 ], abnormal bone formation [ 51 ], root resorption [ 52 ], ankyloses [ 53 ], ectopic bone formation [ 50 ], gingival swelling [ 54 ], etc.…”
Section: Resultsmentioning
confidence: 99%
“…Although multiphasic scaffold strategies seem to be well-suited for periodontal tissue engineering and regeneration in terms of their ability to stimulate coordinated responses in both soft and hard tissues, there is a scarcity of work and apparent limitations. First, as most of the multiphasic constructs were made solely from (Galli et al, 2021).…”
Section: Next-generation Biomaterials Design For Periodontal Regenera...mentioning
confidence: 99%
“…The specific spatial or temporal delivery of signaling molecules, such as growth factors, can be challenging. To overcome those limitations, various gene therapies have been developed specifically for periodontal diseases, allowing for sustained synthesis and secretion of one or multiple growth factors by genetically modifying cells (Figure 4 ) (Galli et al, 2021 ).…”
Section: Development Of Next‐generation Regenerative Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation